A modified mica powder / resin composite insulating material and its preparation process and mica roll preparation process

Zr-Mg-Al oxide inorganic nanoparticles were prepared by using an ultra-fast high-temperature Joule heating furnace in mica powder, and combined with the synergistic effect of modified silane coupling agent and a variety of mica powders, the easy decomposition of mica powder at high temperature was solved. and poor compatibility problems, the insulation and mechanical properties of modified mica powder/resin composites are significantly improved.

CN118919191BActive Publication Date: 2025-01-07SHANGHAI TONGLI ELECTRICAL MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411404645.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-07
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

Mica powder is prone to decomposition and aging at high temperatures, and has poor compatibility with the resin matrix, which leads to poor dispersion in polymers and makes it difficult to exert excellent insulation properties.

Method used

The Zr-Mg-Al oxide inorganic nanoparticles were prepared by ultra-fast high-temperature Joule heating furnace, and the interface bonding performance between mica powder and resin was improved by modifying silane coupling agent, combining mica, gold and black mica. Synergistically, prepare modified mica powder/resin composite insulation material.

Benefits of technology

It significantly improves the insulation performance, heat resistance, mechanical strength and toughness of the material, and improves the dispersion and insulation effect of mica powder in composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118919191B_ABST
    Figure CN118919191B_ABST
Patent Text Reader

Abstract

The present invention relates to a modified mica powder / resin composite insulating material and a preparation process thereof and a mica roll preparation process. The present invention uses Joule heat technology to prepare Zr-Mg-Al oxide, which is named as insulating inorganic nanoparticles. The insulating inorganic nanoparticles prepared by the present invention have excellent electrical insulation performance, heat resistance and chemical stability. It is applied to the preparation of modified mica powder / resin composite insulating materials, which has excellent insulating effect. On the other hand, the present invention significantly improves the mechanical properties of the material by selecting a suitable silane coupling agent for reasonable modification treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of insulating materials, and mainly relates to a preparation process of a modified mica powder / resin composite insulating material, and in particular to a preparation process of a modified mica powder / resin composite insulating material and a mica roll. Background Art

[0002] Mica is a natural mineral belonging to layered silicate minerals with unique physical and chemical properties. Mica is known for its transparent or translucent flake form, good electrical insulation and heat resistance. Therefore, mica is widely used in many industries due to its unique physical and chemical properties.

[0003] Mica powder is a non-metallic mineral containing a variety of components, mainly SiO2, which has a content of about 49%, and A12O3 generally contains about 30%. It has good elasticity and insulation properties, and is resistant to high temperatures, acids and alkalis. It is an excellent filler and is widely used in coatings, ceramics, electrical and other industries. Mica powder is an inorganic mineral with hydrophilic and oleophobic properties. Like most natural minerals, the polarity of the surface of mica powder is relatively large, and its compatibility with the resin matrix is ​​poor. It is difficult to wet and disperse in the organic phase. Directly adding a large amount of mica powder to the polymer will cause the performance of the material to deteriorate, and the advantages of mica cannot be brought into play. Modifying mica powder by physical or chemical methods can improve the problem of poor dispersibility of mica powder to a certain extent. The surface-modified mica powder is more helpful for improving the performance of the matrix. The preparation method of modified mica insulating materials is usually aimed at improving the basic properties of mica, such as improving its electrical insulation, heat resistance, mechanical strength, etc. Summary of the invention

[0004] In order to solve the problem that mica products are prone to decomposition and aging at high temperatures in the related art, and to enable mica powder to be used as an inorganic filler to achieve the best effect of improving the performance of photocurable resin, the present invention provides a preparation process of a modified mica powder / resin composite insulating material, comprising the following steps:

[0005] S1. Weigh zirconium nitrate, magnesium chloride and aluminum hydroxide in a mass ratio of 3:2:3 or 5:1:2, and weigh a total mass of 30-45 g, and dissolve them in 220 mL of deionized water to obtain a precursor solution; then add 2-4 g of urea and 1-3 g of ethylenediaminetetraacetic acid as a complexing agent to the precursor solution and stir until completely dissolved, and then spray dry the solution through a spray dryer, set the inlet air temperature to 150-180 ° C, and the outlet air temperature to 145 ° C, to obtain a dry precursor powder containing Zr-Mg-Al;

[0006] S2. Using a specially made ultrafast high-temperature Joule heating furnace, the precursor powder obtained in step S1 is evenly spread on the conductive substrate graphite paper to ensure that the powder layer thickness is 0.8 mm. The initial current density is set to 800 A / cm², the heating rate is 110 K / s, and the target temperature is 2500 °C. After turning on the power, the Joule effect is used to instantly heat the temperature to the target temperature and maintain it for 3-5 seconds. Then, high-pressure helium is used as a cooling medium. After reaching the predetermined temperature, the power is immediately cut off and high-pressure helium is introduced for quenching treatment at a cooling rate of 100 K / s. The quenched alloy powder is separated and collected from the substrate by mechanical vibration, and then alternately washed with anhydrous ethanol and deionized water for 10 times. The washed powder is placed in a vacuum oven to dry, and then sieved through a 80-100 mesh sieve to obtain Zr-Mg-Al oxide, i.e., insulating inorganic nanoparticles. The insulating inorganic nanoparticles prepared in this step have excellent electrical insulation properties, heat resistance and chemical stability. It is applied to the preparation of modified mica powder / resin composite insulation materials, which has excellent insulation effect.

[0007] S3, while placing the insulating inorganic nanoparticles prepared in step S2 into a vacuum drying oven heated to 80°C to dry the water, 5-8 g of 3-aminopropyltriethoxysilane (APTES), 4-6 g of vinyltriethoxysilane (VTES) and 3-7 g of 3-glycidyloxypropyltrimethoxysilane (KH550) are added to 108-135 g of deionized water and 70-80 g of ethanol, mixed evenly, and stirred at a speed of 400 rpm for 30-45 min to obtain a modified silane coupling agent; the modified silane coupling agent prepared in this step is a chemical additive used to improve the interfacial bonding performance between mica powder and organic material resin. By using a modified silane coupling agent, the water resistance, heat resistance, weather resistance, bonding strength and mechanical properties of the composite material can be significantly improved. The present invention significantly improves the insulation performance and toughness of the material by selecting a suitable silane coupling agent and performing a reasonable modification treatment. Since inorganic nanoparticles have a higher surface energy when filled, the insulation effect of the material will be further improved.

[0008] S4, weigh 13-15 g of muscovite, 10-23 g of phlogopite and 17-21 g of biotite, mix them evenly, ball mill for 3 hours, wash and dry them, put them into a three-necked flask filled with 800-1000 mL of ethanol, stir and disperse them for 40-50 minutes, put them into a water bath heated to 70-85°C, add 50-70 ml of the modified silane coupling agent prepared in step S3 into the three-necked flask, use an electric stirrer to stir the reaction for 50-110 minutes, and then take them out; filter the solution, wash off the ethanol on the surface, dry it for 100-150 minutes, grind and sieve to obtain the modified mica insulating material.

[0009] S5, weigh bisphenol A epoxy resin: cyclopropyl acrylate: polyurethane acrylate resin in a mass ratio of 5:3:2 or 4:3:2, put them into a vacuum drying oven and heat them at 80°C to reduce their viscosity, and the total mass of the composite resin is 30-45g; weigh 8-17% of the total mass of the composite resin prepared in step S4, add the modified mica insulation material to the mixed resin, stir mechanically for 50-75 minutes, and mix evenly; weigh 1-3 g of benzoin ethyl ether and 2-5 g of 2-hydroxy-2-methyl-1-phenylacetone, stir mechanically for 10-32 minutes, and then cast them into a specific mold to make them evenly distributed in the mold, use ultraviolet light equipment to irradiate for 14-32 seconds to complete curing, and cool to obtain a modified mica powder / resin composite insulation material. In this step, a low-viscosity, low-molecular-weight, easy-to-process and mixed liquid resin is selected. The present invention uses Joule heat technology to prepare Zr-Mg-Al oxide, which is named as insulating inorganic nanoparticles. The insulating inorganic nanoparticles prepared by the present invention have excellent electrical insulation performance, heat resistance and chemical stability. It is applied to the preparation of modified mica powder / resin composite insulating materials, which has excellent insulation effect. On the other hand, the present invention significantly improves the insulation performance and toughness of the material by selecting a suitable silane coupling agent and performing reasonable modification treatment. Since the surface energy of the inorganic nanoparticles is high when they are filled, agglomeration is more likely to occur, which will further improve the insulation effect of the material.

[0010] S6, putting the modified mica insulating material prepared in step S4 into a pulping machine, crushing and pulping it with high-pressure water at a pressure of 5-8 MPa, and dehydrating the prepared modified mica pulp by graded dewatering with three dewatering screens of 50 mesh, 80 mesh, and 200 mesh, and the obtained 50-80 mesh and 80-200 mesh two kinds of coarse and fine pulps enter the pulp storage tank, and are stored separately for standby; papermaking: regulating the sizing order of the modified mica coarse pulp and the modified mica fine pulp, sequentially performing the first sizing of the modified mica fine pulp, the sizing of the modified mica coarse pulp, and then the second sizing of the mica fine pulp, and finally performing round-net papermaking, drying the prepared modified mica paper, and drying it to a moisture content of 0.3-0.6% to obtain modified calcined muscovite mica paper, wherein the sizing amount of the modified mica fine pulp is the same for the two times, and the mass ratio of the mica coarse pulp to the mica fine pulp during sizing is controlled to be 2:1;

[0011] S7. The back of the polyester film is subjected to corona treatment, and a self-adhesive is coated thereon and then dried. After drying, an adhesive is coated thereon and the modified calcined mica paper is compounded by heating and pressurizing at 150-170°C, and then the mica roll is rolled up after drying.

[0012] Preferably, the ball milling process parameters of the present invention are: ball milling medium: zirconium oxide balls, diameter 10 mm, ball-to-material ratio: 10:1, speed: 70% of the critical speed, grinding time: 2 h, material loading: filling rate 30%. Equipment: planetary ball mill, capacity 1 liter.

[0013] Preferably: the ultraviolet curing equipment of the present invention is Fusion UV Systems (F600S).

[0014] Preferably, the "specific casting mold" in step S5 of the present invention is a model of 10cm*15cm*15cm.

[0015] Preferably: The specially made ultrafast high temperature Joule heating furnace of the present invention is purchased from Advanced Energy Industries, Inc.

[0016] Preferably: the polyester film in step S7 is purchased from Henan Dongjue Electric Co., Ltd., and the coating adhesive is purchased from Shandong Guohua Chemical Co., Ltd.

[0017] Preferably, the dimensions of the polyester film in step S7 are: a thickness of 50 μm or 100 μm, a width of 300 mm or 500 mm, and a length supplied in roll form.

[0018] Preferably, the process parameters for applying the self-adhesive in step S7 are: temperature: 30-35°C, time: 4-6 h, stirring speed: 300 rpm, coating method: roller coating, coating thickness: 30 μm, coating speed: 50-80 m / min. Drying method: hot air drying, drying temperature: 80°C, drying time: 3-5 min.

[0019] Pressurized lamination, pressure: 0.5-0.8 MPa, lamination speed: 50-60 m / min, lamination temperature: 60°C. Winding tension control: 5-8 N / mm, to ensure that the tension of the substrate is moderate during winding to avoid wrinkles and breaks. Roll diameter: 600 mm. Roll length: 500 meters. Slitting, slitting width: 20-25 mm, slitting speed: 30-35 m / min. Self-adhesive mica roll product dimensions: thickness: 0.5 mm, width: 20 mm, length: 500 meters.

[0020] Preferably, the process parameters of the corona treatment in step S7 are voltage: 8-10 kV, current: 20-40 mA, treatment time: 5-12 s, treatment speed: 25-45 m / min, electrode spacing: 10 mm, environmental conditions: temperature 25°C, relative humidity 50%.

[0021] Preferably: in the step S1, zirconium nitrate, magnesium chloride and aluminum hydroxide are weighed in a mass ratio of 3:2:3, and the total mass is 30 g, which are dissolved in 220 mL of deionized water to obtain a precursor solution; then, 2 g of urea and 1 g of ethylenediaminetetraacetic acid are added to the precursor solution as complexing agents and stirred until completely dissolved, and then the solution is spray dried by a spray dryer, and the inlet air temperature is set to 150 ° C and the outlet air temperature is set to 145 ° C, to obtain a dry precursor powder containing Zr-Mg-Al;

[0022] Preferably: in the step S1, zirconium nitrate, magnesium chloride and aluminum hydroxide are weighed respectively in a mass ratio of 5:1:2, and the total mass weighed is 45 g, which are dissolved in 220 mL of deionized water to obtain a precursor solution; then, 4 g of urea and 3 g of ethylenediaminetetraacetic acid are added to the precursor solution as complexing agents and stirred until completely dissolved, and then the solution is spray dried by a spray dryer, and the inlet air temperature is set to 180 ° C and the outlet air temperature is set to 145 ° C to obtain a dry precursor powder containing Zr-Mg-Al.

[0023] Preferably: in the step S2, a special ultrafast high-temperature Joule heating furnace is used to evenly spread the precursor powder obtained in step S1 on the conductive substrate graphite paper to ensure that the powder layer thickness is 0.8 mm, the initial current density is set to 800A / cm², the heating rate is 110 K / s, the target temperature is 2500°C, and after turning on the power, the Joule effect is used to instantly heat the temperature to the target temperature and maintain it for 3-5 s; then high-pressure helium is used as a cooling medium, and after reaching the predetermined temperature, the power is immediately cut off and high-pressure helium is introduced for quenching treatment, and the cooling rate is 100 K / s; the quenched alloy powder is separated and collected from the substrate by mechanical vibration, and then alternately washed with anhydrous ethanol and deionized water for 10 times, the washed powder is placed in a vacuum oven to dry, and then sieved through an 80-mesh sieve to obtain Zr-Mg-Al oxide, which is named insulating inorganic nanoparticles.

[0024] Preferably: in the step S3, while the insulating inorganic nanoparticles prepared in the step S2 are placed in a vacuum drying oven heated to 80° C. to dry the moisture, 5 g of 3-aminopropyltriethoxysilane (APTES), 6 g of vinyltriethoxysilane (VTES) and 3 g of 3-glycidyloxypropyltrimethoxysilane (KH550) are added to 135 g of deionized water and 70 g of ethanol, mixed evenly, and stirred at a speed of 400 rpm for 30 min to obtain a modified silane coupling agent.

[0025] Preferably: in the step S3, while the insulating inorganic nanoparticles prepared in the step S2 are placed in a vacuum drying oven heated to 80° C. to dry the moisture, 8 g of 3-aminopropyltriethoxysilane (APTES), 6 g of vinyltriethoxysilane (VTES) and 7 g of 3-glycidyloxypropyltrimethoxysilane (KH550) are added to 135 g of deionized water and 80 g of ethanol, mixed evenly, and stirred at a speed of 400 rpm for 45 min to obtain a modified silane coupling agent.

[0026] Preferably: in the step S4, 13 g of muscovite, 10 g of phlogopite and 17 g of biotite are weighed and mixed evenly, then ball-milled for 3 h, washed and dried, placed in a three-necked flask containing 800 mL of ethanol, stirred and dispersed for 40 min, placed in a water bath heated to 70 ° C, 50 ml of the modified silane coupling agent prepared in step S3 is added to the three-necked flask, stirred with an electric stirrer for 50 min, and then taken out; the solution is filtered, the ethanol on the surface is washed off, dried for 100 min, and the modified mica insulating material can be obtained after grinding and sieving.

[0027] Preferably: in the step S4, 15 g of muscovite, 23 g of phlogopite and 21 g of biotite are weighed and mixed evenly, then ball-milled for 3 h, washed and dried, placed in a three-necked flask containing 1000 mL of ethanol, stirred and dispersed for 50 min, placed in a water bath heated to 85° C., 70 ml of the modified silane coupling agent prepared in step S3 is added to the three-necked flask, stirred with an electric stirrer for 110 min, and then taken out; the solution is filtered, the ethanol on the surface is washed off, dried for 150 min, and the modified mica insulating material can be obtained after grinding and sieving.

[0028] Preferably: in the step S5, bisphenol A epoxy resin: cyclopropyl acrylate: polyurethane acrylate resin are weighed in a mass ratio of 4:3:2, placed in a vacuum drying oven at 80°C and heated to reduce the viscosity, and the total mass of the composite resin is 45 g; the modified mica insulating material prepared in step S4 with a mass ratio of 17% is weighed respectively, added to the mixed resin, mechanically stirred for 75 minutes, and mixed evenly; 3 g of benzoin ethyl ether and 2 g of 2-hydroxy-2-methyl-1-phenylpropanone are weighed, mechanically stirred for 32 minutes, and then cast into a specific mold to make them evenly distributed in the mold, and irradiated with ultraviolet light equipment for 32 seconds to complete curing, and cooled to obtain a modified mica powder / resin composite insulating material.

[0029] Preferably: in the step S5, bisphenol A epoxy resin: cyclopropyl acrylate: polyurethane acrylate resin are weighed in a mass ratio of 5:3:2, placed in a vacuum drying oven at 80°C and heated to reduce the viscosity, and the total mass of the composite resin is 30 g; the modified mica insulating material prepared in step S4, which accounts for 8% of the total mass of the composite resin, is weighed, added to the mixed resin, mechanically stirred for 50 min, and mixed evenly; 1 g of benzoin ethyl ether and 2 g of 2-hydroxy-2-methyl-1-phenylpropanone are weighed, mechanically stirred for 10 min, and then cast into a specific mold to make them evenly distributed in the mold, and irradiated with ultraviolet light equipment for 14 s to complete curing, and cooled to obtain a modified mica powder / resin composite insulating material.

[0030] Preferably: the chemicals described in the present invention are all purchased from Aladdin Reagent (Shanghai) Co., Ltd.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1. The Zr-Mg-Al oxide (insulating inorganic nanoparticles) prepared by the present invention has excellent electrical insulation performance, heat resistance and chemical stability.

[0033] 2. The present invention adopts an ultrafast high-temperature Joule heating furnace for heating, which has a fast material preparation speed and obtains better material particles, which is conducive to better dispersion into the mica insulating material.

[0034] 3. The present invention adopts a uniform mixture of muscovite, phlogopite and biotite, which can give full play to the synergistic effect between different mica powders and improve the mechanical strength of the material.

[0035] 4. The present invention is simple to operate and is suitable for the needs of industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0037] Figure 1 This is a scanning image of the insulating inorganic nanoparticles prepared in Example 1 of the present invention.

[0038] Figure 2 This is a scanning image of the insulating inorganic nanoparticles prepared in Comparative Example 1 of the present invention.

[0039] Figure 3 This is a scanning image of the insulating inorganic nanoparticles prepared in Comparative Example 2 of the present invention.

[0040] Figure 4 The infrared spectra of the modified mica insulating materials prepared in Example 3 of the present invention and Comparative Examples 7 and 8 are shown.

[0041] Figure 5 : The wetting angles of the modified mica powder / resin composite insulating materials prepared in Example 3 and Comparative Example 9 of the present invention.

[0042] Figure 6 The present invention is a process flow chart for preparing mica rolls. DETAILED DESCRIPTION

[0043] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the content of the present invention and are not used to limit the present invention.

[0044] Example 1

[0045] S1. Weigh zirconium nitrate, magnesium chloride and aluminum hydroxide in a mass ratio of 3:2:3, respectively, and weigh a total mass of 30 g, and dissolve them in 220 mL of deionized water to obtain a precursor solution; then add 2 g of urea and 1 g of ethylenediaminetetraacetic acid as complexing agents to the precursor solution and stir until completely dissolved, then spray dry the solution through a spray dryer, set the inlet air temperature to 150 °C and the outlet air temperature to 145 °C, and obtain a dry precursor powder containing Zr-Mg-Al;

[0046] S2. Using a specially made ultrafast high-temperature Joule heating furnace, the precursor powder obtained in step S1 is evenly spread on the conductive substrate graphite paper to ensure that the powder layer thickness is 0.8 mm. The initial current density is set to 800 A / cm², the heating rate is 110 K / s, and the target temperature is 2500 °C. After turning on the power, the Joule effect is used to instantly heat the temperature to 2500 °C and maintain it for 5 s. Then, high-pressure helium is used as a cooling medium. After reaching 1000 °C, the power is immediately cut off and high-pressure helium is introduced for quenching treatment at a cooling rate of 100 K / s. The quenched alloy powder is separated and collected from the substrate by mechanical vibration, and then alternately washed with anhydrous ethanol and deionized water for 10 times. The washed powder is placed in a vacuum oven to dry, and then sieved through an 80-mesh sieve to obtain Zr-Mg-Al oxide, which is named insulating inorganic nanoparticles. The insulating inorganic nanoparticles prepared in this step have excellent electrical insulation properties, heat resistance and chemical stability. It is applied to the preparation of modified mica powder / resin composite insulation materials, which has excellent insulation effect.

[0047] S3, while placing the insulating inorganic nanoparticles prepared in step S2 into a vacuum drying oven heated to 80°C to dry the water, 5 g of 3-aminopropyltriethoxysilane (APTES), 4 g of vinyltriethoxysilane (VTES) and 3 g of 3-glycidyloxypropyltrimethoxysilane (KH550) were added to 108 g of deionized water and 70 g of ethanol, mixed evenly and stirred at a speed of 400 rpm for 30 min to obtain a modified silane coupling agent; the modified silane coupling agent prepared in this step is a chemical additive for improving the interfacial bonding performance between mica powder and organic material resin. By using a modified silane coupling agent, the water resistance, heat resistance, weather resistance, bonding strength and mechanical properties of the composite material can be significantly improved. The present invention significantly improves the insulation performance and toughness of the material by selecting a suitable silane coupling agent and performing a reasonable modification treatment. Since the surface energy of inorganic nanoparticles is high when they are filled, agglomeration is more likely to occur, which will further enhance the insulation effect of the material.

[0048] S4, weigh 13 g of muscovite, 10 g of phlogopite and 17 g of biotite, mix them evenly, ball mill for 3 h, wash and dry them, put them into a three-necked flask filled with 800 mL of ethanol, stir and disperse them for 40 min, put them into a water bath heated to 70 ° C, add 50-70 ml of the modified silane coupling agent prepared in step S3 into the three-necked flask, use an electric stirrer to stir the reaction for 50 min and then take them out; filter the solution, wash off the ethanol on the surface, dry it for 100 min, grind and sieve to obtain the modified mica insulating material;

[0049] S5. Weigh bisphenol A epoxy resin: cyclopropyl acrylate: polyurethane acrylate resin in a mass ratio of 5:3:2, heat in a vacuum drying oven at 80°C to reduce its viscosity, and the total mass of the composite resin is 30 g; weigh the modified mica insulating material prepared in step S4 in a mass ratio of 8%, add it to the mixed resin, stir mechanically for 50 min, and mix evenly; weigh 1 g of benzoin ethyl ether and 2 g of 2-hydroxy-2-methyl-1-phenylpropanone, stir mechanically for 10 min, and then pour them into a 10cm*15cm*15cm model to make them evenly distributed in the mold, use ultraviolet light equipment to irradiate for 14 s to complete curing, and cool to obtain a modified mica powder / resin composite insulating material.

[0050] Comparative Example 1: Except that zirconium nitrate is not added in step S1, the remaining steps are the same as those in Example 1.

[0051] Comparative Example 2: Except that magnesium chloride is not added in step S1, the remaining steps are the same as those in Example 1.

[0052] Figure 1 This is a scanning image of the insulating inorganic nanoparticles prepared in Example 1 of the present invention. Figure 2 This is a scanning image of the insulating inorganic nanoparticles prepared in Comparative Example 1 of the present invention. Figure 3 This is a scanning image of the insulating inorganic nanoparticles prepared in comparative example 2 of the present invention. From the analysis of the scanning image, it can be seen that the insulating inorganic nanoparticles prepared by the present invention are small spheres. Compared with comparative examples 1 and 2, the small spheres of the insulating inorganic nanoparticles prepared in Example 1 are more evenly dispersed and have a better appearance. The insulating inorganic nanoparticles prepared in comparative examples 1 and 2 without adding zirconium or magnesium elements are relatively chaotic and disordered, and the dispersion between the spheres is uneven, which is not conducive to its application in the preparation of modified mica powder / resin composite insulating materials. It can be seen that in the present invention, the atomic sizes of Zr and Mg are different, and there is a certain synergistic effect between the two. After rapid heating using Joule heat, the prepared Zr-Mg-Al oxide has a better granular feel and is more conducive to dispersion in mica powder / resin composite insulating materials, thereby improving its insulation and mechanical properties.

[0053] Example 2

[0054] S1. Weigh zirconium nitrate, magnesium chloride and aluminum hydroxide in a mass ratio of 5:1:2, with a total mass of 45 g, and dissolve them in 220 mL of deionized water to obtain a precursor solution; then add 4 g of urea and 3 g of ethylenediaminetetraacetic acid as complexing agents to the precursor solution and stir until completely dissolved, then spray dry the solution through a spray dryer, set the inlet air temperature to 180 °C and the outlet air temperature to 145 °C, and obtain a dry precursor powder containing Zr-Mg-Al;

[0055] S2. Using a specially made ultrafast high-temperature Joule heating furnace, the precursor powder obtained in step S1 is evenly spread on the conductive substrate graphite paper to ensure that the powder layer thickness is 0.8 mm. The initial current density is set to 800 A / cm², the heating rate is 110 K / s, and the target temperature is 2500 °C. After turning on the power, the Joule effect is used to instantly heat the temperature to 2500 °C and maintain it for 3 s. Then, high-pressure helium is used as a cooling medium. After reaching 1000 °C, the power is immediately cut off and high-pressure helium is introduced for quenching treatment at a cooling rate of 100 K / s. The quenched alloy powder is separated and collected from the substrate by mechanical vibration, and then alternately washed with anhydrous ethanol and deionized water for 10 times. The washed powder is placed in a vacuum oven to dry, and then sieved through a 100-mesh sieve to obtain Zr-Mg-Al oxide, which is named insulating inorganic nanoparticles. The insulating inorganic nanoparticles prepared in this step have excellent electrical insulation properties, heat resistance and chemical stability. It is applied to the preparation of modified mica powder / resin composite insulation materials, which has excellent insulation effect.

[0056] S3, while placing the insulating inorganic nanoparticles prepared in step S2 into a vacuum drying oven heated to 80°C to dry the water, 8 g of 3-aminopropyltriethoxysilane (APTES), 6 g of vinyltriethoxysilane (VTES) and 7 g of 3-glycidyloxypropyltrimethoxysilane (KH550) were added to 135 g of deionized water and 80 g of ethanol, mixed evenly and stirred at a speed of 400 rpm for 45 min to obtain a modified silane coupling agent; the modified silane coupling agent prepared in this step is a chemical additive for improving the interfacial bonding performance between mica powder and organic material resin. By using a modified silane coupling agent, the water resistance, heat resistance, weather resistance, bonding strength and mechanical properties of the composite material can be significantly improved. The present invention significantly improves the insulation performance and toughness of the material by selecting a suitable silane coupling agent and performing a reasonable modification treatment. Since the surface energy of inorganic nanoparticles is high when they are filled, agglomeration is more likely to occur, which will further enhance the insulation effect of the material.

[0057] S4, weigh 15 g of muscovite, 23 g of phlogopite and 21 g of biotite, mix them evenly, ball mill for 3 h, wash and dry them, put them into a three-necked flask filled with 1000 mL of ethanol, stir and disperse them for 50 min, put them into a water bath heated to 85°C, add 70 ml of the modified silane coupling agent prepared in step S3 into the three-necked flask, stir and react with an electric stirrer for 110 min, and then take them out; filter the solution, wash off the ethanol on the surface, dry them for 150 min, grind and sieve them to obtain the modified mica insulating material;

[0058] S5. Weigh bisphenol A epoxy resin: cyclopropyl acrylate: polyurethane acrylate resin in a mass ratio of 4:3:2, heat in a vacuum drying oven at 80°C to reduce its viscosity, and the total mass of the composite resin is 45 g; weigh the modified mica insulating material prepared in step S4 in a mass ratio of 17%, add it to the mixed resin, stir mechanically for 75 min, and mix evenly; weigh 3 g of benzoin ethyl ether and 5 g of 2-hydroxy-2-methyl-1-phenylpropanone, stir mechanically for 32 min, and then pour them into a 10 cm*15 cm*15 cm model to make them evenly distributed in the mold, irradiate with ultraviolet light equipment for 32 s to complete curing, and cool to obtain a modified mica powder / resin composite insulating material.

[0059] Comparative Example 3: Except that aluminum hydroxide is not added in step S1, the remaining steps are the same as those in Example 2.

[0060] Comparative Example 4: S1. Weigh zirconium nitrate, magnesium chloride, and aluminum hydroxide in a mass ratio of 5:1:2, respectively, with a total mass of 45 g, and dissolve them in 220 mL of deionized water to obtain a precursor solution; then add 4 g of urea and 3 g of ethylenediaminetetraacetic acid as complexing agents to the precursor solution and stir until completely dissolved, then spray dry the solution through a spray dryer, set the inlet air temperature to 180 ° C, and the outlet air temperature to 145 ° C, to obtain a dry precursor powder containing Zr-Mg-Al;

[0061] S2. Put the precursor powder obtained in step S1 into a muffle furnace, heat it to 950° C. at a rate of 5° C. / min, and calcine it for 110 min to obtain Zr-Mg-Al oxide, which is named insulating inorganic nanoparticles.

[0062] S3, while placing the insulating inorganic nanoparticles prepared in step S2 into a vacuum drying oven heated to 80°C to dry the water, 8 g of 3-aminopropyltriethoxysilane (APTES), 6 g of vinyltriethoxysilane (VTES) and 7 g of 3-glycidyloxypropyltrimethoxysilane (KH550) were added to 135 g of deionized water and 80 g of ethanol, mixed evenly and stirred at a speed of 400 rpm for 45 min to obtain a modified silane coupling agent; the modified silane coupling agent prepared in this step is a chemical additive for improving the interfacial bonding performance between mica powder and organic material resin. By using a modified silane coupling agent, the water resistance, heat resistance, weather resistance, bonding strength and mechanical properties of the composite material can be significantly improved. The present invention significantly improves the insulation performance and toughness of the material by selecting a suitable silane coupling agent and performing a reasonable modification treatment. Since the surface energy of inorganic nanoparticles is high when they are filled, agglomeration is more likely to occur, which will further enhance the insulation effect of the material.

[0063] S4, weigh 15 g of muscovite, 23 g of phlogopite and 21 g of biotite, mix them evenly, ball mill for 3 h, wash and dry them, put them into a three-necked flask filled with 1000 mL of ethanol, stir and disperse them for 50 min, put them into a water bath heated to 85°C, add 70 ml of the modified silane coupling agent prepared in step S3 into the three-necked flask, stir and react with an electric stirrer for 110 min, and then take them out; filter the solution, wash off the ethanol on the surface, dry them for 150 min, grind and sieve them to obtain the modified mica insulating material;

[0064] S5. Weigh bisphenol A epoxy resin: cyclopropyl acrylate: polyurethane acrylate resin in a mass ratio of 4:3:2, heat them in a vacuum drying oven at 80°C to reduce their viscosity, and the total mass of the composite resin is 45 g; weigh the modified mica insulating material prepared in step S4 in a mass ratio of 17%, add them to the mixed resin, stir them mechanically for 75 min, and mix them evenly; weigh 3 g of benzoin ethyl ether and 5 g of 2-hydroxy-2-methyl-1-phenylpropanone, stir them mechanically for 32 min, and then cast them into a specific mold to make them evenly distributed in the mold, irradiate them with ultraviolet light equipment for 32 s to complete curing, and cool them to obtain a modified mica powder / resin composite insulating material.

[0065] Comparative Example 5: Except that the insulating inorganic nanoparticles (Zr—Mg—Al oxide) in step S3 are replaced by commercial silicon dioxide, the remaining steps are the same as those in Example 2.

[0066] Comparative Example 6: Except for not adding insulating inorganic nanoparticles in step S3, the remaining steps are the same as those in Example 2.

[0067] Determination of volume resistivity: Volume resistivity refers to the ratio of the DC voltage applied to the two surfaces of a unit volume of an insulating material to the steady-state current passing through the insulating material. Resistivity test in the present invention: The test is carried out in accordance with GB / T31838.2-2019, and the temperature is (23+2)°C. The entry of various stray currents during the test causes the resistivity of the sample to fluctuate, and the test environment of the present invention remains uniform. Table 1 shows the volume resistivity of the modified mica powder / resin composite insulating materials prepared in Examples 1 and 2 of the present invention and Comparative Examples 1-6. As can be seen from the figure, the preparation method of the insulating inorganic nanoparticles in the present invention and the type of Zr-Mg-Al element added have a great influence on the resistivity of the material. The volume resistivity of the modified mica powder / resin composite insulating materials prepared in Examples 1 and 2 of the present invention are 4.87±0.22×10 15 Ω·m and 5.02±0.12×10 15 Ω·m. It is much larger than the volume resistivity of the modified mica powder / resin composite insulating material prepared in Comparative Examples 1-6. It shows that the mica powder / resin composite insulating material prepared by the present invention has the best insulating performance. The Joule heat rapid heating technology combined with Zr-Mg-Al oxide (insulating inorganic nanoparticles) can greatly improve the insulating performance of mica materials. When used as the main insulating material, it can improve work efficiency and reduce the occurrence of safety accidents.

[0068] Table 1

[0069]

[0070] Example 3

[0071] S1. Weigh zirconium nitrate, magnesium chloride and aluminum hydroxide in a mass ratio of 3:2:3, respectively, with a total mass of 36 g, and dissolve them in 220 mL of deionized water to obtain a precursor solution; then add 3 g of urea and 2 g of ethylenediaminetetraacetic acid as complexing agents to the precursor solution and stir until completely dissolved, then spray dry the solution through a spray dryer, set the inlet air temperature to 165 °C and the outlet air temperature to 145 °C, and obtain a dry precursor powder containing Zr-Mg-Al;

[0072] S2. Using a specially made ultrafast high-temperature Joule heating furnace, the precursor powder obtained in step S1 is evenly spread on the conductive substrate graphite paper to ensure that the powder layer thickness is 0.8 mm. The initial current density is set to 800 A / cm², the heating rate is 110 K / s, and the target temperature is 2500 °C. After turning on the power, the Joule effect is used to instantly heat the temperature to 2500 °C and maintain it for 4 s. Then, high-pressure helium is used as a cooling medium. After reaching 1000 °C, the power is immediately cut off and high-pressure helium is introduced for quenching treatment at a cooling rate of 100 K / s. The quenched alloy powder is separated and collected from the substrate by mechanical vibration, and then alternately washed with anhydrous ethanol and deionized water for 10 times. The washed powder is placed in a vacuum oven to dry, and then sieved through a 100-mesh sieve to obtain Zr-Mg-Al oxide, which is named insulating inorganic nanoparticles. The insulating inorganic nanoparticles prepared in this step have excellent electrical insulation properties, heat resistance and chemical stability. It is applied to the preparation of modified mica powder / resin composite insulation materials, which has excellent insulation effect.

[0073] S3, while placing the insulating inorganic nanoparticles prepared in step S2 into a vacuum drying oven heated to 80°C to dry the water, add 7 g of 3-aminopropyltriethoxysilane (APTES), 5 g of vinyltriethoxysilane (VTES) and 6 g of 3-glycidyloxypropyltrimethoxysilane (KH550) to 125 g of deionized water and 75 g of ethanol, mix well and stir at a speed of 400 rpm for 37 min to obtain a modified silane coupling agent; the modified silane coupling agent prepared in this step is a chemical additive for improving the interfacial bonding performance between mica powder and organic material resin. By using a modified silane coupling agent, the water resistance, heat resistance, weather resistance, bonding strength and mechanical properties of the composite material can be significantly improved. The present invention significantly improves the insulation performance and toughness of the material by selecting a suitable silane coupling agent and performing a reasonable modification treatment. Since the surface energy of inorganic nanoparticles is high when they are filled, agglomeration is more likely to occur, which will further enhance the insulation effect of the material.

[0074] S4, weigh 14 g of muscovite, 19 g of phlogopite and 19 g of biotite, mix them evenly, ball mill for 3 h, wash and dry them, put them into a three-necked flask filled with 800-1000 mL of ethanol, stir and disperse them for 44 min, put them into a water bath heated to 77 ° C, add 68 ml of the modified silane coupling agent prepared in step S3 into the three-necked flask, use an electric stirrer to stir the reaction for 75 min, and then take them out; filter the solution, wash off the ethanol on the surface, dry it for 140 min, grind and sieve it to obtain the modified mica insulating material;

[0075] S5. Weigh bisphenol A epoxy resin: cyclopropyl acrylate: polyurethane acrylate resin in a mass ratio of 4:3:2, heat in a vacuum drying oven at 80°C to reduce its viscosity, and the total mass of the composite resin is 38 g; weigh the modified mica insulating material prepared in step S4 in a mass ratio of 15%, add it to the mixed resin, stir mechanically for 66 min, and mix evenly; weigh 2 g of benzoin ethyl ether and 4 g of 2-hydroxy-2-methyl-1-phenylacetone, stir mechanically for 22 min, and then pour them into a 10 cm*15 cm*15 cm model to make them evenly distributed in the mold, use ultraviolet light equipment to irradiate for 19 s to complete curing, and cool to obtain a modified mica powder / resin composite insulating material.

[0076] Comparative Example 7: Except that 7 g of 3-aminopropyltriethoxysilane (APTES) is not added in step S3, the remaining steps are the same as those in Example 3.

[0077] Comparative Example 8: Except that 5 g of vinyltriethoxysilane (VTES) was not added in step S3, the remaining steps were the same as those in Example 3.

[0078] Comparative Example 9: Except that 6 g of 3-glycidyloxypropyltrimethoxysilane (KH550) was not added in step S3, the remaining steps were the same as those in Example 3.

[0079] Figure 4 The infrared spectra of the modified mica insulating materials prepared in Example 3 and Comparative Examples 7 and 8 of the present invention are shown in FIG. 1 . As can be seen from the figure, the mica powder modified in the present invention has an infrared spectrum of 2931 cm -1 、3368cm -1 There is an obvious characteristic absorption peak at 2931cm -1 It can be attributed to the absorption peak caused by CH vibration. -1 The characteristic absorption peak of C=O appears at 3368cm -1 The characteristic peak at is the OH characteristic absorption peak, which is significantly weakened in Example 3, indicating that the silane coupling agent successfully coated the mica. Figure 5 The wetting angles of the modified mica powder / resin composite insulating materials prepared in Example 3 of the present invention and Comparative Example 9. Analysis shows that the contact angle of Example 3 is much larger than that of Comparative Example 9. This indicates that the modified mica powder / resin composite insulating material of the present invention has good hydrophobicity, enhanced lipophilicity, and a larger contact angle. In short, the mixed modification of 3-aminopropyltriethoxysilane (APTES), vinyltriethoxysilane (VTES) and 3-glycidyloxypropyltrimethoxysilane (KH550) in the present invention improves the wettability of the mica powder / resin composite insulating material and enhances the market competitiveness of the material.

[0080] Example 4

[0081] S1. Weigh zirconium nitrate, magnesium chloride and aluminum hydroxide in a mass ratio of 5:1:2, with a total mass of 39 g, and dissolve them in 220 mL of deionized water to obtain a precursor solution; then add 3 g of urea and 2 g of ethylenediaminetetraacetic acid as complexing agents to the precursor solution and stir until completely dissolved, then spray dry the solution through a spray dryer, set the inlet air temperature to 177 °C and the outlet air temperature to 145 °C, and obtain a dry precursor powder containing Zr-Mg-Al;

[0082] S2. Using a specially made ultrafast high-temperature Joule heating furnace, the precursor powder obtained in step S1 is evenly spread on the conductive substrate graphite paper to ensure that the powder layer thickness is 0.8 mm. The initial current density is set to 800 A / cm², the heating rate is 110 K / s, and the target temperature is 2500 °C. After turning on the power, the Joule effect is used to instantly heat the temperature to 2500 °C and maintain it for 5 s. Then, high-pressure helium is used as a cooling medium. After reaching 1000 °C, the power is immediately cut off and high-pressure helium is introduced for quenching treatment at a cooling rate of 100 K / s. The quenched alloy powder is separated and collected from the substrate by mechanical vibration, and then alternately washed with anhydrous ethanol and deionized water for 10 times. The washed powder is placed in a vacuum oven to dry, and then sieved through a 100-mesh sieve to obtain Zr-Mg-Al oxide, which is named insulating inorganic nanoparticles. The insulating inorganic nanoparticles prepared in this step have excellent electrical insulation properties, heat resistance and chemical stability. It is applied to the preparation of modified mica powder / resin composite insulation materials, which has excellent insulation effect.

[0083] S3, while placing the insulating inorganic nanoparticles prepared in step S2 into a vacuum drying oven heated to 80°C to dry the water, add 7 g of 3-aminopropyltriethoxysilane (APTES), 5 g of vinyltriethoxysilane (VTES) and 6 g of 3-glycidyloxypropyltrimethoxysilane (KH550) to 115 g of deionized water and 76 g of ethanol, mix well, and stir at a speed of 400 rpm for 38 min to obtain a modified silane coupling agent; the modified silane coupling agent prepared in this step is a chemical additive for improving the interfacial bonding performance between mica powder and organic material resin. By using a modified silane coupling agent, the water resistance, heat resistance, weather resistance, bonding strength and mechanical properties of the composite material can be significantly improved. The present invention significantly improves the insulation performance and toughness of the material by selecting a suitable silane coupling agent and performing a reasonable modification treatment. Since the surface energy of inorganic nanoparticles is high when they are filled, agglomeration is more likely to occur, which will further enhance the insulation effect of the material.

[0084] S4, weigh 14 g of muscovite, 17 g of phlogopite and 19 g of biotite, mix them evenly, ball mill for 3 h, wash and dry them, put them into a three-necked flask filled with 900 mL of ethanol, stir and disperse them for 47 min, put them into a water bath heated to 79 ° C, add 69 ml of the modified silane coupling agent prepared in step S3 into the three-necked flask, use an electric stirrer to stir the reaction for 80 min, and then take them out; filter the solution, wash off the ethanol on the surface, dry it for 140 min, grind and sieve it to obtain the modified mica insulating material;

[0085] S5. Weigh bisphenol A epoxy resin: cyclopropyl acrylate: polyurethane acrylate resin in a mass ratio of 4:3:2, heat in a vacuum drying oven at 80°C to reduce its viscosity, and the total mass of the composite resin is 36 g; weigh the modified mica insulating material prepared in step S4 in a mass ratio of 16%, add it to the mixed resin, stir mechanically for 66 min, and mix evenly; weigh 2 g of benzoin ethyl ether and 4 g of 2-hydroxy-2-methyl-1-phenylacetone, stir mechanically for 19 min, and then pour them into a 10 cm*15 cm*15 cm model to make them evenly distributed in the mold, use ultraviolet light equipment to irradiate for 27 s to complete curing, and cool to obtain a modified mica powder / resin composite insulating material.

[0086] Another aspect of the present invention is to prepare a mica roll product:

[0087] S6, putting the modified mica insulating material prepared in step S4 into a pulping machine, crushing and pulping it with high-pressure water at a pressure of 6MPa, and dehydrating the prepared modified mica pulp by graded dewatering with three dewatering screens of 50 mesh, 80 mesh, and 200 mesh, and the obtained 50-80 mesh and 80-200 mesh two kinds of coarse and fine pulps enter the pulp storage tank, and are stored separately for standby; papermaking: regulating the sizing order of the modified mica coarse pulp and the modified mica fine pulp, sequentially performing the first sizing of the modified mica fine pulp, the sizing of the modified mica coarse pulp, and then the second sizing of the mica fine pulp, and finally performing round-net papermaking, drying the prepared modified mica paper, and drying it to a moisture content of 0.3% to obtain modified calcined muscovite mica paper, wherein the sizing amount of the modified mica fine pulp is the same for the two times, and the mass ratio of the mica coarse pulp to the mica fine pulp during sizing is controlled to be 2:1;

[0088] S7. The back of the polyester film is subjected to corona treatment, coated with self-adhesive and then dried, and then coated with adhesive and the modified calcined mica paper is heated and pressurized at 150°C for compounding, and then dried, rolled and slit to obtain a self-adhesive mica roll product.

[0089] Comparative Example 10: Except that bisphenol A epoxy resin is not added in step S3, the remaining steps are the same as those in Example 4.

[0090] Comparative Example 11: Except that cyclopropyl acrylate is not added in step S3, the remaining steps are the same as those in Example 4.

[0091] Comparative Example 12: Except that no polyurethane acrylate resin is added in step S3, the remaining steps are the same as those in Example 4.

[0092] The mechanical properties of mica rolls are tested: Tensile strength test: Tensile strength test usually refers to stretching the material until it breaks to measure the maximum stress it withstands, so as to evaluate the mechanical properties of the material. First, cut or form samples of specific sizes according to the test standard, usually in the shape of strips or dog bones. Specifically, the sample is cut into a total length of 250 mm, a gauge length of 50 mm, and a width of 12.7 mm. Install the sample on a universal materials testing machine, making sure that the clamp fixes both ends of the sample, and then start stretching the sample until it breaks, and record the stress (force divided by the original cross-sectional area) and strain (elongation divided by the original length) of the sample. The maximum stress that a material can withstand during stretching is usually measured in Pascals (Pa) or Megapascals (MPa). The calculation formula is as follows: Tensile strength ( σ )=F / A0, where F is the maximum force the sample can withstand when it breaks, in Newtons; A0 is the original cross-sectional area of ​​the sample (square centimeters, cm²).

[0093] Tear strength test: Cut the material into samples of specific size, specifically a total length of 75 mm, a gauge length of 25 mm, and a width of 19 mm. Fix one side of the sample in the upper fixture of the tear tester, and leave a part of the other side of the sample for tearing. Apply a gradually increasing force at the free end of the sample, which is perpendicular to the edge of the sample to simulate the tearing process. Continue to increase the load until the sample tears, and record the maximum load during the tearing process. Record the maximum load during the tearing process and the size of the sample; tear strength = F max / L, where Fmax is the maximum load recorded when the sample is torn, in N; L is the length of the torn portion of the sample, in cm. To eliminate experimental contingency, the experiment was tested 8 times, and the test results are shown in Table 2.

[0094] Table 2

[0095]

[0096] According to the test in Table 2, there is a certain synergistic effect between bisphenol A epoxy resin, cyclopropyl acrylate and polyurethane acrylate resin. When mixed in a certain proportion, they can effectively activate the mica surface and improve the toughness of the mica roll. The method of alternating fine slurry and coarse slurry can obtain a mica roll with better tensile strength and tear strength.

[0097] Breakdown field strength measurement: The ZJC-KV instrument manufactured by Beijing AVIC Times Instrument Equipment Co., Ltd. was used to test the breakdown strength. The experiment was carried out in air, and the voltage increase rate at the power frequency was 0.2kV / s. The breakdown voltage obtained in the experiment was in kV, and then divided by the thickness of the paper to obtain the breakdown strength in kV / mm. The breakdown strength was calculated according to the formula E=U / d, where E is the breakdown strength, kV / mm; U is the breakdown voltage, kV; and d is the paper thickness, mm. The test results are shown in Table 3.

[0098] Table 3

[0099]

[0100] The breakdown field strength directly reflects the insulation performance of the insulating material. The greater the breakdown field strength, the greater the maximum electric field strength that the insulating material can withstand, and the better the insulation performance. Table 3 shows the breakdown strength of the modified mica powder / resin composite insulating materials prepared in Example 4 of the present invention and Comparative Examples 10-12. The breakdown field strength of the composite insulating material in Example 4 is the largest, which is 23.56 kV / mm. The nanoparticles in the modified mica powder / resin composite insulating material prepared by the present invention are not prone to agglomeration, and the composite material insulation is difficult to decompose and destroy under various effects, and has a strong breakdown resistance.

[0101] The above-mentioned embodiments only express the specific implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present invention. It should be pointed out that, for those skilled in the art, without departing from the concept of the present invention, any other changes, modifications, substitutions, combinations, simplifications made without departing from the spirit and principle of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A process for preparing a modified mica powder / resin composite insulating material, characterized in that: The steps include: S1. Weigh zirconium nitrate, magnesium chloride and aluminum hydroxide in a mass ratio of 3:2:3 or 5:1:2, weigh a total mass of 30-45 g of the drugs, dissolve them in 220 mL of deionized water to obtain a precursor solution; then add 2-4 g of urea and 1-3 g of ethylenediaminetetraacetic acid as complexing agents to the precursor solution and stir until completely dissolved, then spray dry the solution through a spray dryer, set the inlet air temperature to 150-180 °C, and the outlet air temperature to 145 °C, to obtain a dry precursor powder containing Zr-Mg-Al; S2. Using a Joule heating furnace, evenly spread the precursor powder obtained in step S1 on the conductive substrate graphite paper to ensure that the powder layer thickness is 0.8 mm, set the initial current density to 800 A / cm², the heating rate to 110 K / s, and the target temperature to 2500 ℃. After turning on the power, use the Joule effect to instantly heat up to the target temperature and maintain it for 3-5 s; then use helium as a cooling medium. After reaching the predetermined temperature, immediately cut off the power and introduce helium for quenching treatment at a cooling rate of 100 K / s; use mechanical vibration to separate and collect the quenched alloy powder from the substrate, then wash it alternately with anhydrous ethanol and deionized water for 10 times, place the washed powder in a vacuum oven to dry, and then sieve it through a 80-100 mesh sieve to obtain Zr-Mg-Al oxide, which is named insulating inorganic nanoparticles; S3, while placing the insulating inorganic nanoparticles prepared in step S2 into a vacuum drying oven heated to 80° C. to dry the water, 5-8 g of 3-aminopropyltriethoxysilane, 4-6 g of vinyltriethoxysilane and 3-7 g of 3-glycidyloxypropyltrimethoxysilane are added to 108-135 g of deionized water and 70-80 g of ethanol, the mixture is evenly mixed and stirred at a speed of 400 rpm for 30-45 min to obtain a modified silane coupling agent; S4, weigh 13-15 g of muscovite, 10-23 g of phlogopite and 17-21 g of biotite, mix them evenly, ball mill for 3 h, wash and dry them, put them into a three-necked flask filled with 800-1000 mL of ethanol, stir and disperse them for 40-50 min, put them into a water bath heated to 70-85 ° C, add 50-70 ml of the modified silane coupling agent prepared in step S3 into the three-necked flask, use an electric stirrer to stir the reaction for 50-110 min, and then take them out; filter the solution, wash off the ethanol on the surface, dry it for 100-150 min, grind and sieve to obtain the modified mica insulating material; S5. Weigh bisphenol A epoxy resin: cyclopropyl acrylate: polyurethane acrylate resin in a mass ratio of 5:3:2 or 4:3:2, heat in a vacuum drying oven at 80°C to reduce its viscosity, and the total mass of the composite resin is 30-45 g; weigh 8-17% of the total mass of the composite resin prepared in step S4, add the modified mica insulating material to the mixed resin, stir mechanically for 50-75 min, and mix evenly; add 1-3 g of benzoin ethyl ether and 2-5 g of 2-hydroxy-2-methyl-1-phenylacetone, stir mechanically for 10-32 min, then cast into a mold to make it evenly distributed in the mold, irradiate with ultraviolet light equipment for 14-32 seconds to complete curing, and cool to obtain a modified mica powder / resin composite insulating material.

2. The process for preparing a modified mica powder / resin composite insulating material according to claim 1, characterized in that: In the step S1, zirconium nitrate, magnesium chloride and aluminum hydroxide are weighed in a mass ratio of 3:2:3, with a total mass of 30 g, which are dissolved in 220 mL of deionized water to obtain a precursor solution; then, 2 g of urea and 1 g of ethylenediaminetetraacetic acid are added to the precursor solution as complexing agents and stirred until completely dissolved, and then the solution is spray dried by a spray dryer, with the inlet air temperature set at 150 °C and the outlet air temperature set at 145 °C, to obtain a dry precursor powder containing Zr-Mg-Al.

3. The process for preparing a modified mica powder / resin composite insulating material according to claim 1, characterized in that: In the step S1, zirconium nitrate, magnesium chloride and aluminum hydroxide are weighed in a mass ratio of 5:1:2, with a total mass of 45 g, which are dissolved in 220 mL of deionized water to obtain a precursor solution; then, 4 g of urea and 3 g of ethylenediaminetetraacetic acid are added to the precursor solution as complexing agents and stirred until completely dissolved, and then the solution is spray dried by a spray dryer, with the inlet air temperature set to 180°C and the outlet air temperature set to 145°C, to obtain a dry precursor powder containing Zr-Mg-Al.

4. The process for preparing a modified mica powder / resin composite insulating material according to claim 1, characterized in that: In the step S2, a Joule heating furnace is used to evenly spread the precursor powder obtained in step S1 on the conductive substrate graphite paper, ensuring that the powder layer thickness is 0.8 mm, setting the initial current density to 800 A / cm², the heating rate to 110 K / s, and the target temperature to 2500°C. After turning on the power, the Joule effect is used to instantly heat the temperature to the target temperature and maintain it for 3-5 s; then helium is used as a cooling medium, and after reaching the predetermined temperature, the power is immediately cut off and helium is introduced for quenching treatment, and the cooling rate is 100 K / s; the quenched alloy powder is separated and collected from the substrate by mechanical vibration, and then alternately washed with anhydrous ethanol and deionized water for 10 times, the washed powder is placed in a vacuum oven to dry, and then sieved through an 80-mesh sieve to obtain Zr-Mg-Al oxide, which is named insulating inorganic nanoparticles.

5. The process for preparing a modified mica powder / resin composite insulating material according to claim 1, characterized in that: In the step S3, while the insulating inorganic nanoparticles prepared in the step S2 are placed in a vacuum drying oven heated to 80° C. to dry the moisture, 5 g of 3-aminopropyltriethoxysilane, 6 g of vinyltriethoxysilane and 3 g of 3-glycidyloxypropyltrimethoxysilane are added to 135 g of deionized water and 70 g of ethanol, mixed evenly, and stirred at a speed of 400 rpm for 30 min to obtain a modified silane coupling agent.

6. The process for preparing a modified mica powder / resin composite insulating material according to claim 1, characterized in that: In the step S3, while the insulating inorganic nanoparticles prepared in the step S2 are placed in a vacuum drying oven heated to 80° C. to dry the moisture, 8 g of 3-aminopropyltriethoxysilane, 6 g of vinyltriethoxysilane and 7 g of 3-glycidyloxypropyltrimethoxysilane are added to 135 g of deionized water and 80 g of ethanol, mixed evenly, and stirred at a speed of 400 rpm for 45 min to obtain a modified silane coupling agent.

7. The process for preparing a modified mica powder / resin composite insulating material according to claim 1, characterized in that: In the step S4, 13 g of muscovite, 10 g of phlogopite and 17 g of biotite are weighed and mixed evenly, then ball-milled for 3 h, washed and dried, placed in a three-necked flask containing 800 mL of ethanol, stirred and dispersed for 40 min, and then placed in a water bath heated to 70° C., 50 ml of the modified silane coupling agent prepared in step S3 is added to the three-necked flask, stirred with an electric stirrer for reaction for 50 min, and then taken out; the solution is filtered, the ethanol on the surface is washed off, dried for 100 min, and the modified mica insulating material can be obtained after grinding and sieving.

8. The process for preparing a modified mica powder / resin composite insulating material according to claim 1, characterized in that: In the step S5, bisphenol A epoxy resin: cyclopropyl acrylate: polyurethane acrylate resin are weighed in a mass ratio of 4:3:2, placed in a vacuum drying oven at 80°C and heated to reduce the viscosity thereof, and the total mass of the composite resin is 45 g; the modified mica insulating material prepared in step S4, which accounts for 17% of the total mass of the composite resin, is weighed, added to the mixed resin, and mechanically stirred for 75 minutes to mix evenly; 3 g of benzoin ethyl ether and 2 g of 2-hydroxy-2-methyl-1-phenylpropanone are weighed, mechanically stirred for 32 minutes, and then cast into a mold to make them evenly distributed in the mold, and irradiated with an ultraviolet light device for 32 seconds to complete curing, and cooled to obtain a modified mica powder / resin composite insulating material.

Citation Information

Patent Citations

  • Solid power cosmetic

    JP1990295913A

  • Composite resin composition and molded product having excellent insulation properties and heat dissipation properties

    JP2014109024A